PEMASARAN DIGITAL BERKELANJUTAN MEMBANGUN BRAND YANG RAMAH LINGKUNGAN - Andri Catur Trissentianto; Mujito Mujito (Institut Teknologi dan Bisnis Dewantara, 2025)
The increasing consumer awareness of environmental issues has encouraged companies to implement digital marketing strategies oriented toward sustainability. The main problem addressed in this study is how companies can utilize digital strategies to build environmentally friendly brands. The objective of this study is to explore the selection of appropriate digital channels, the creation of content that supports sustainability values, and the measurement of campaign impact on brand image. The benefit of this research is to provide insights for companies in developing marketing strategies that are not only effective for business but also environmentally responsible. The findings show that sustainable digital marketing, when carried out authentically and measurably, can enhance consumer engagement and strengthen brand positioning in a market that is increasingly concerned with sustainability.